2021
DOI: 10.1186/s12879-021-06589-4
|View full text |Cite
|
Sign up to set email alerts
|

From first to second wave: follow-up of the prospective COVID-19 cohort (KoCo19) in Munich (Germany)

Abstract: Background In the 2nd year of the COVID-19 pandemic, knowledge about the dynamics of the infection in the general population is still limited. Such information is essential for health planners, as many of those infected show no or only mild symptoms and thus, escape the surveillance system. We therefore aimed to describe the course of the pandemic in the Munich general population living in private households from April 2020 to January 2021. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
(37 reference statements)
1
16
1
1
Order By: Relevance
“…In its first round (July to August 2020), the study estimated that there were 1.8 times as many infections as reported by health authorities 23 . While first local seroepidemiological studies in Germany, which were mainly conducted in hotspot areas, indicated underascertainment ratios of four to five 2,7,24-26 , starting with the second half of 2020 underascertainment ratios were lower, in the majority of studies underascertainment was around two 22,23,[27][28][29][30][31] . The Robert Koch Institute as the national Public Health Institute systematically tracks seroepidemiological studies in the general population as well as in special population groups conducted in Germany (http:// www.…”
Section: Discussionmentioning
confidence: 99%
“…In its first round (July to August 2020), the study estimated that there were 1.8 times as many infections as reported by health authorities 23 . While first local seroepidemiological studies in Germany, which were mainly conducted in hotspot areas, indicated underascertainment ratios of four to five 2,7,24-26 , starting with the second half of 2020 underascertainment ratios were lower, in the majority of studies underascertainment was around two 22,23,[27][28][29][30][31] . The Robert Koch Institute as the national Public Health Institute systematically tracks seroepidemiological studies in the general population as well as in special population groups conducted in Germany (http:// www.…”
Section: Discussionmentioning
confidence: 99%
“…Hence we may have underestimated seroprevalence post second wave in Highfield because some individuals with recent or current infection may not yet have seroconverted. Seroprevalence may have been underestimated due to antibody decay over time [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In its first round (July to August 2020), the study estimated that there were 1.8 times as many infections as reported by health authorities 23 . While first local seroepidemiological studies in Germany, which were mainly conducted in hotspot areas, indicated underascertainment ratios of four to five 2,7,24-26 , starting with the second half of 2020 underascertainment ratios were lower, in the majority of studies underascertainment was around two 22,23,[27][28][29][30][31] . The Robert Koch Institute as the national Public Health Institute systematically tracks seroepidemiological studies in the general population as well as in special population groups conducted in Germany (www.rki.de/covid-19-serostudies-germany).…”
Section: Discussionmentioning
confidence: 99%